Energy spectra in $p$-shell $Λ$ hypernuclei and $^{19}_{Λ}F$ and spin-dependent $Λ N$ interactions. (7th July 2019) - Kanada-En'yo, Yoshiko; Isaka, Masahiro; Motoba, Toshio
Abstract: Energy spectra of$0s$ -orbit$Λ$ states in$p$ -shell$Λ$ hypernuclei ($^{A}_Λ Z$ ) and those in$^{19}_{Λ}F$ are studied with the microscopic cluster model and antisymmetrized molecular dynamics using the$G$ -matrix effective$Λ N$ ($Λ NG$ ) interactions. Spin-dependent terms of the ESC08a version of the$Λ NG$ interactions are tested and phenomenologically tuned to reproduce observed energy spectra in$p$ -shell$^{A}_Λ Z$ . Spin-dependent contributions of the$Λ N$ interactions to spin-doublet splitting and excitation energies are discussed. Energy spectra for unobserved excited states in$p$ -shell$^{A}_Λ Z$ and$^{19}_{Λ}F$ are predicted with the modified$Λ NG$ interactions.